PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi Pada J&T Express Cabang Kalianyar Surabaya) - Anggieta Rosyida; Winarto; Rini Fatmawati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
Customer loyalty is the key objective of a company since it is long-term and significantly influences the company’s existence. Shipping businesses, as service providers, are expected to pay attention to the requirements and wishes of clients who have established expectations. On the other hand, customer loyalty is difficult to achieve; therefore, businesses must employ a variety of strategies to achieve it. Service quality is one of the strategies employed in service organizations, and customer loyalty is believed to be established by offering excellent service quality. This study aimed to determine the effect of service quality on customer loyalty in J&T Express, Branch of Kalianyar-Surabaya. The hypothesis was that service quality has a significant impact on customer loyalty. The type of study was explanatory research, and the research method was quantitative with an associative approach. Questionnaires were used to gather data, and test data analysis was assisted by the SPSS application Customers who utilized J&T Express more than once and made deliveries between Surabaya’s cities were included in this study as samples. Hypothesis testing revealed that service quality, including tangible evidence, reliability, responsiveness, assurance, and empathy, has both a partial and simultaneous effect. Adjusted R Square value showed the service quality has an effect of 81.7% on customer loyalty. Multiple linear regression analysis results in physical evidence, reliability, and responsiveness variables have a strong relationship, while assurance and empathy have a weak relationship with customer loyalty.